Chlorination Behaviors of Some Metal Sulfides as Investigated by Thermogravimetric Analysis - R. Titi-Manyaka; I. Iwasaki (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
Chlorination and chloridization behaviors of pyrite, pyrrhotite, marcasite, chalcocite, covellite, galena, sphalerite, heazlewoodite, and elemental sulfur were investigated by thermogravimetric analysis. The possible reaction mechanisms are discussed on the basis of the theoretical weight changes and thermodynamic considerations. Chlorine is a more effective chloridizing agent than hydrogen chloride. In the light of the experimental results, a scheme for producing nonferrous metal chlorides, molten sulfur, and ferric oxide from complex sulfide flotation concentrates is discussed.